BINGO GAMES METHOD Upaya Meningkatkan Kemampuan Siswa Memecahkan Masalah Belajar Matematika - Bali, Muhammad Mushfi El Iq (Penerbit STKIP PGRI Bangkalan, 2019)
Based on the results of observations of researchers, learning Mathematics in class IV MI Nurul Yaqin Probolinggo is known that after students receive the operating concept material to calculate the multiplication and division, students are instructed to do intensive practice exercises. As a result, students' interest in learning is reduced, so students are less interested in learning multiplication and division material. Efforts can be made to overcome problems related to the learning climate, researchers experimented to implement the BINGO game method. This study aims to describe the implementation of learning by using BINGO games to improve students' ability to solve learning problems and improve mathematics learning outcomes in class IV MI Nurul Yaqin. Students' ability to solve Mathematics learning problems through BINGO games can be applied to students who have heterogeneous academic abilities. Implementation of learning is able to improve student learning outcomes to the maximum. In addition, the BINGO game is also able to increase the enthusiasm and activity of students so that students are motivated and happy in learning the content of Mathematics.